Profile of Patients under Mechanical Ventilation in ICU during COVID-19 Pandemic: a Hospital Based Study - Bhattarai, Ramesh; Mahashat, Nirajan; Rawal, Mangal; Pandey, Kabita; Devkota, Harihar; Dhakal , Sita; Pyakurel, Kumud (Journal of Karnali Academy of Health Sciences, 2020)
Background: COVID-19 has become unprecedented challenge to ICU management. The measures for containment of the disease and mitigation can be possible only with a proper and organized planning. This study was conducted to evaluate the profile of mechanically ventilated patient in ICU of a Hospital in remote high altitude region during this pandemic.Methods: A cross-sectional study was done in patients who were admitted and managed with intubation and mechanical ventilation in ICU of Karnali Academy of Health Sciences (KAHS). Data were collected and filled in per-forma. Data were filled in Microsoft Excel and analysis done. Result: Most of the cases were adult males with 50% average intubation days less than five. Out of the total 42 cases 67% were intubated for inadequate airway protection and 33% `for respiratory failure. PCR test for COVID-19 was done for 50% of cases and one patient got positive result. Mortality was around 50% among intubated patients in ICU.Conclusion: ICU services at Karnali Academy of Health Sciences have been provided for both COVID and non-COVID patients during the pandemic. Referral hospital ICUs in remote part are important in management of serious cases of those areas during any pandemic so they should be well prepared.